Association between HIV status and Positive Prostate Biopsy in a Study of U.S. Veterans. (2009) - Hsiao, Wayland; Anastasia, Katrina; Hall, John; Goodman, Michael; Rimland, David; Ritenour, Chad W. M.; Issa, Muta M.
Abstract : HIV infection is associated with increased incidence of malignancies, such as lymphomas and testicular cancers. We reviewed the relationship between HIV infection and prostate cancer in a contemporary series of prostate biopsy patients. The study is a retrospective analysis of consecutive prostate biopsies performed at a VA Medical Center. The indications for performing a prostate biopsy included an abnormal digital rectal examination and/or an elevated PSA. Patients were categorized according to their HIV status, biopsy results, and various demographic and clinical characteristics. Univariate and multivariate analyses compared distributions of HIV status, and various clinical and demographic characteristics. The adjusted measures of association between HIV status and positive biopsy were expressed as odds ratios (ORs) and corresponding 95% confidence intervals (CI). The likelihood of positive biopsy was significantly higher among 18 HIV-positive patients compared to patients with negative HIV tests (adjusted OR = 3.9; 95% CI: 1.3–11.5). In analyses restricted to prostate cancer patients, HIV-positive patients were not different from the remaining group with respect to their prostate cancer stage, PSA level, PSA velocity, PSA density, or Gleason grade. There is an association between HIV infection and prostate biopsy positive for carcinoma in a population referred for urologic workup. Further confirmation of this association by prospective studies may impact the current screening practices in HIV patients.